Lift of Cambered Flapping Wing Inspired by Bats - Yusoff, Hamid; Iswadi Ismail, Noor; Shuib, Solehuddin; Rozi Mat Nawi, Muhad; Suhaimi, Shafiq (International Journal of Engineering and Technology, 2018)
In this paper, a bio-mimic approach was used to help characterise a flapping wing for the design of a Micro Air Vehicle (MAV). The main objective of this study is to characterise the lift performance of a flapping wing inspired by bat wings at different angle of attack (AoA), advance ratio (J) and wing camber. A series of flapping bat wings with different wing camber (flat, 6% camber, 9% camber, 12% camber, and 15% camber) was tested for its time averaged lift (CLavg) at AoA of 0â° to 50â° and at three different advance ratios which are; 0.88 (unsteady state regime), 1.76 (steady state regime), 3.09 (steady state regime). The result shows that as the advance ratio increases, the generated CLavg begins to decay but the enhancement of CLavg between increasing camber increases. This shows that wing camber begins to have a bigger role at higher advance ratio and hold the key to overcoming the adverse effect of high steady state flight regime on a flapping wing.Â Â